REFORMS AND PROSPECTS IN THE FIELD OF EDUCATION IN UZBEKISTAN (International conference on multidisciplinary science, 2023)
This article reflects on positive changes and innovations in the system as a result of many innovations and reforms in the family education system in our country in recent years.